THE SIX-MINUTE WALKING TEST FOR MEASURING VITAL LUNG CAPACITY AND VO2 MAX IN TEENAGERS IN THE NURSING ANESTHESIOLOGY DEPARTMENT - Rohmah, Astika Nur; Dewi, Ratih Kusuma; Prihatin, Hajutri (Jurnal Kesehatan Kusuma Husada, 2025)
Background: Technological advances are making activities easier. The convenience gained hurts daily life, such as laziness in exercise and reluctance to gather and communicate actively, especially among teenagers. Physical fitness is essential in improving cardiovascular health, including heart and blood vessel endurance and vital lung capacity. Maximum oxygen volume (VO2 max) can be used to assess a person’s cardiorespiratory endurance. This study aimed to use a 6-minute walk test to measure VO2 max and the lungs’ vital capacity. Methods: The method used a pre-experiment with total sampling, namely 118 student respondents. These tools include emergency equipment, a stopwatch to calculate running time, colourful markers to indicate the path, and traffic cones for additional markers, using the Borg Breathing Difficulty Scale to check how difficult it is for respondents to breathe. Analysis used the Wilcoxon test because the normality assumption is not met.Results: The results showed that the relationship between the distance of the 6-minute walk test and vital lung capacity was indicated by a p-value of 0.000 (P<0.05), and the relationship between the distance of the 6-minute walk test and VO2 max was marked by a p-value of 0.000 (P<0.05). Physical fitness is essential in improving cardiovascular health, including heart and blood vessel endurance and lung vital capacity. Conclusion: This study concludes that there is a relationship between the 6-minute walk test and vital lung capacity and VO2 max.